Antifungal Hydrogels: Living Bacteria in Thermoresponsive Gel for Treating Fungal Infections (Adv. Funct. Mater. 40/2018). (1st October 2018) - Lufton, Maayan; Bustan, Or; Eylon, Bat‐hen; Shtifman‐Segal, Ella; Croitoru‐Sadger, Tsuf; Shagan, Alona; Shabtay‐Orbach, Ayelet; Corem‐Salkmon, Enav; Berman, Judith; Nyska, Abraham; Mizrahi, Boaz
Abstract : In article number1801581, Boaz Mizrahi and co‐workers report an anti‐fungal delivery system based on secreting bacteria inside a thermo‐responsive hydrogel. The formula hardens after administration whereas bacteria continuously produce antifungal agents and deliver them in situ. This system could provide an efficient and safe alternative to traditional fungal infection treatments.